Hindgut microbiota profiling and functional prediction of sheep (Ovis aries) fed with different dietary calcium levels - Muhammad Khan; Xiaoqi Zhao; Xiaojun Ni; Baiji Danzeng; Sikandar Ali; Maida Mushtaq; Hongyuan Yang; Jiachong Liang; Syed Khurram Fareed; Bai Xue; Guobo Quan (Scientific Reports)
Abstract Hindgut microbiota plays a crucial role in small ruminant health and productivity, with diet being a key influencing factor. This study aimed to investigate the hindgut microbiota profile and functional prediction in sheep fed with different dietary calcium levels. Thirty male Yunnan Semi-Fine Wool rams (10 months old, 40.37 ± 0.49 kg) were randomly assigned to three dietary calcium levels: 0.53% (Q_1), 0.74% (Q_3), and 0.98% (Q_5) on a dry matter basis. On day 21, fecal samples (n = 9/group) were analyzed via 16S rRNA sequencing. Alpha diversity metrics showed higher species richness and evenness in Q_5 (p < 0.05), while beta diversity analysis (Bray–Curtis/UniFrac) demonstrated distinct difference between groups (PERMANOVA, p = 0.001). Taxonomic profiling identified Firmicutes and Bacteroidetes as dominant phyla (60–80% relative abundance), with Q_5 enriched in SCFA-producers (Faecalibacterium, Roseburia) and Q_3 favoring mucin-degrading Bacteroides. Differential abundance analysis confirmed these patterns, revealing significant enrichment of Ruminococcaceae_UCG-010 and Eubacterium coprostanoligenes. Functional prediction linked these taxonomic shifts to metabolic specialization: Q_5 showed elevated butyrate production pathways (pyruvate fermentation: + 1.8 log2FC), while Q_3 had enhanced nucleotide biosynthesis (purine pathways, p < 0.01). These findings suggest that dietary calcium modulates hindgut microbiota, influencing metabolic pathways linked to energy production and protein synthesis, with potential benefits for sheep productivity.